Optimasi Pola Operasi Waduk Sutami Menggunakan Model Pemrograman Linier Kabur (Fuzzy Linear Programming) - Abel, Yenson Priyadi; Rispiningtati, Rispiningtati; Soetopo, Widandi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2015)
Sutami Reservoir is located in Karangkates Village, Sumber Pucung District, Malang Regency. Its primary benefits are for flood control, irrigation, power generation of 3 x 35 MW, and to supply a minimum discharge of 56 m 3 /sec for downstream regions. Early on, it was planned that the minimum discharge for the hydropower turbine would be 25 m /sec and the maximum discharge would be 51.39 m 3 /sec. In its 40 years of age, the turbine has only been capable of handling a maximum discharge of 46.09 m 3 /sec. Electricity production can be maintained by optimizing the outflow that enters the turbine. A model was designed using a fuzzy linear programming model, which is combined with a simulation model for reservoir operating rule performance evaluation. In this study, an optimization of 11 years was obtained, in the form of optimal energy production of 5606.66 GWh, a new rule curve for the regulation of water surface levels, and a simulated result of 100% reliability for the model and existing implementation.Keywords : Fuzzy linear programming, optimization, simulation, reservoir operation rule, Sutami reservoir.